The Suspicious Copy of Khayyam and Graves - Allovidinovna, Ishankulova Diyora (Journal of Innovation in Education and Social Research, 2025)
This article explores the intriguing encounter between Robert Graves, a renowned British poet and scholar, and a suspicious copy of the Rubaiyat of Omar Khayyam. Graves’s investigation into this manuscript, believed to be a more authentic or original version of the famous Persian work, raises important questions regarding literary authenticity, translation, and the preservation of ancient texts. Through examining the context of the Rubaiyat's various translations, particularly Edward Fitzgerald’s, the article sheds light on Graves’s fascination with uncovering hidden truths in historical manuscripts and his deep engagement with the legacy of Khayyam's poetry.